Analysis of the Implementation of the People's School Program Policy Using the Van Meter Model and the Van Horn Model in Indonesia - Muhammad Giri Ramanda Nazaputra Kiemas; Raniasa Putra; Katriza Imania; Muhammad Nurbudyanto (Journal of Business, Social and Technology, 2026)
Background: The implementation of public policy is a crucial stage that determines whether or not a policy succeeds in achieving the goals that have been set. Objective: This study analyzes the implementation of the People's School Program initiated by the government and run through the Ministry of Social Affairs of the Republic of Indonesia as an instrument of social intervention to break the chain of poverty through access to free education. The program is aimed at children from poor and extreme poor families, especially those who refer to the bottom decile group of the government's social database. Methods: This study uses a descriptive qualitative approach based on literature studies. The analytical framework used is the Van Meter and Van Horn policy implementation model which emphasizes six main variables, namely policy standards and goals, resources, inter-organizational communication, characteristics of implementing agencies, socio-economic-political environmental conditions, and implementer disposition. Results: The results of the analysis show that the People's School Program has a strong and clear policy direction in terms of objectives, but the success of its implementation is still highly determined by the consistency of cross-ministry coordination, the readiness of human resources, the quality of infrastructure, the validity of the beneficiary database, and the supervision of implementation at the field level. Conclusion: The results of the study conclude that Sekolah Rakyat has the potential to be a transformative social policy model, but its long-term effectiveness depends on strengthening governance implementation, continuous monitoring, and integration between actors.